VOC uptakes on gypsum boards: Sorption performances and impact on indoor air quality. (June 2018) - Thevenet, F.; Debono, O.; Rizk, M.; Caron, F.; Verriele, M.; Locoge, N.
Abstract: Indoor air pollution requires the development of various approaches to reduce the concentration of VOCs. Beyond the optimization of ventilation and the reduction of pollutant sources, building materials with sorptive properties are currently examined as possible VOC remediation processes. The potentialities and the effectiveness of sorptive building materials still require detailed and reliable assessments. Thus, the objective of this paper relies in the development of a methodology to determine VOC partitioning coefficients on two sorptive building materials, in comparison with a non-sorptive one, using two contrasted model VOCs, namely toluene and formaldehyde, under different environmental indoor conditions. This approach aims at comparing the different materials and estimating their lifetimes regarding VOC uptake under realistic indoor conditions. After exposing the experimental methodology, uptakes of toluene and formaldehyde are investigated on the three selected gypsum boards. The determination of respective partitioning coefficients enlightens the contrasted behaviours of boards depending on (i) the presence or absence of sorptive agent in their formulation, (ii) the nature of the sorptive agent used, (iii) the structure of the model VOC, (iv) the paper layer on board and (v) the relative humidity. Based on obtained experimental results, the lifetimes of boards are evaluated for each VOC. Results evidence that improvements still have to be achieved to enhance the significance of sorptive gypsum board on indoor air quality. Nevertheless, reliable methodologies are now available to assess the behavior of these materials in indoor environment and to help their effective optimization. Highlights: Effective and reliable methodology for partitioning coefficient (K) determination. Quantitative determination of K on real building materials for different model VOCs. Evidence of the dependence of K on material nature, environmental conditions and VOC structure. Assessment of sorptive building material lifetimes and impact on indoor air quality.